Trastuzumab and pertuzumab without chemotherapy in early-stage HER2+ breast cancer: a plain language summary of the PHERGain study - Perez-Garcia, Jose Manuel; Gebhart, Geraldine; Borrego, Manuel Ruiz; Schmid, Peter; Marmé, Frederik; Prat, Aleix; Dalenc, Florence; Kerrou, Khaldoun; Colleoni, Marco; Braga, Sofía; Malfettone, Andrea; Sampayo-Cordero, Miguel; et al. (Future oncology, 2022)
What is this summary about? - - This is a summary of a publication about the PHERGain study, which was published in The Lancet Oncology in May 2021. The study includes 376 women with a type of breast cancer called HER2-positive breast cancer that can be removed by surgery. In the study, researchers wanted to learn if participants could be treated with two medicines called trastuzumab and pertuzumab without the need for chemotherapy. To identify HER2-positive tumors with more sensitivity to anti-HER2 therapies, the researchers used a type of imaging called a FDG-PET scan to check how well the treatments were working. - - What happened in the PHERGain study? - - Participants took a treatment before surgery, consisting of either chemotherapy (docetaxel and carboplatin) plus trastuzumab and pertuzumab (group A) or trastuzumab and pertuzumab alone (plus hormone therapy if the tumor was hormone receptor-positive; group B). After two cycles of treatment, participants underwent a FDG-PET scan. Participants assigned to group A completed 6 cycles of treatment regardless of 18F-FDG-PET results. Participants in group B continued the same treatment until surgery if their FDG-PET scan showed the treatment was working. While participants who did not show a response started treatment with chemotherapy in addition to trastuzumab and pertuzumab. All participants then had surgery. - - What were the results? - - The results revealed that, of the participants in group B who showed a response using FDG-PET scan, 37.9% achieved a disappearance of all invasive cancer in the breast and axillary lymph nodes. This rate appears to be higher than those reported in previous studies evaluating the same treatment. These participants also had less side effects and improved overall quality of life compared with participants taking chemotherapy plus trastuzumab and pertuzumab. - - What do the results of the study mean? - - Early monitoring of how well participants respond to treatment by FDG-PET scan seems to identify participants with operable HER2-positive breast cancer who were more likely to benefit from trastuzumab and pertuzumab without the need to have chemotherapy. The PHERGain study is still ongoing and results on long-term survival are expected to be released in 2023. - - Clinical Trial Registration: NCT03161353 (ClinicalTrials.gov)
Gesehen am 21.08.2023